Sosialisasi Cyber Ethicts Dalam Rangka Membangun Literasi Digital Yang Aman Dan Sehat Bagi Masyarakat - Herdiana, Dadan; Anita Lakshana, I Gusti Ayu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2022)
This activity is motivated by the large number of people who do not understand how to use social media safely and healthily, and how parents are able to assist children in using the internet safely and healthily. Therefore, socialization about ethics using the internet is needed, especially in the protection of personal data. Based on these problems, counseling on Cyber Ethics in the Context of Building Safe and Healthy Digital Literacy for the Community was carried out in the Lengkong Wetan Village Office Hall, Serpong, South Tangerang. This activity aims to provide an overview to the public on how to use technology and communication in a healthy manner, as well as to provide an overview of how to use digital applications safely and correctly. This activity was carried out using the extension method in the form of lectures accompanied by interactive discussions between participants and resource persons. Based on the evaluation after the socialization of safe and healthy Cyber Ethics and Digital Literacy for the community, the results showed that there was a very good increase in knowledge and understanding. In conclusion, the activity was successful and gave positive results to the public's understanding of digital literacy. It is recommended that similar activities continue to be carried out so that more people understand the ethics of using digital applications that are safe and healthy for the community, especially personal data protection.